Peran Gender Dalam Memoderasi Pengaruh Status Sosial Ekonomi, Pendidikan Pengelolaan Keuangan Keluarga, Sikap Uang, Teman Sebaya Terhadap Literasi Keuangan - Selawati Septianingtyas; Ahmad Nurkhin (Universitas Negeri Semarang, 2023)
The purpose of this study was to analyze the effect of socioeconomic status, education on family financial management, attitudes towards money and peers on the financial literacy of 2019 students of Economic Education (Accounting) Semarang State University. The population of this research were students of Economic Education (Accounting) UNNES 2019 totaling 115 students, the number of samples in this study was determined by the saturation sampling technique so that the number of samples was 115 students.The data analysis method used is descriptive statistical analysis and Moderated Regression Analysis (MRA). The results of this study indicate that socio-economic status, family financial management education, money attitudes and peer groups have a significant positive affect on financial literacy, gender variables are able to moderate the effect of socioe-conomic status and money attitude on financial literacy, gender variables are not able to moderate the influence of family financial management education and peer groups on financial literacy